Quantitative and qualitative insights into the experiences of children with Rett syndrome and their families - Downs, Jennepher; Leonard, Helen (2016)
Rett syndrome is a rare neurodevelopmental disorder caused by a mutation in the MECP2 gene. It is associated with severe functional impairments and medical comorbidities such as scoliosis and poor growth. The population-based and longitudinal Australian Rett Syndrome Database was established in 1993 and has supported investigations of the natural history of Rett syndrome and effectiveness of treatments, as well as a suite of qualitative studies to identify deeper meanings. This paper describes the early presentation of Rett syndrome, including regression and challenges for families seeking a diagnosis. We discuss the importance of implementing strategies to enhance daily communication and movement, describe difficulties interpreting the presence of pain and discomfort, and argue for a stronger evidence base in relation to management. Finally, we outline a framework for understanding quality of life in Rett syndrome and suggest areas of life to which we can direct efforts in order to improve quality of life. Each of these descriptions is illustrated with vignettes of child and family experiences. Clinicians and researchers must continue to build this framework of knowledge and understanding with efforts committed to providing more effective treatments and supporting the best quality of life for those affected.